TEPUK TEPUNG TAWAR: TRADISI KEBUDAYAAN MASYARAKAT MELAYU RIAU - Rahmadhanty, Rafiqah; Rahmawati, Richa Dwi; Gustiwi, Triska (TSAQIFA NUSANTARA: Jurnal Pembelajaran dan Isu-Isu Sosial, 2024)
Riau is a province in Indonesia with a majority ethnic Malay community. The Malay community has various cultural traditions, one of which is Tepuk Tepung Tawar. Writing this article aims to discuss the Tepuk Tepung Tawar tradition and the meaning contained in carrying out this tradition. Data collection was carried out using the library research method and interviews conducted with the Chairperson of the Pelalawan Traditional Malay Institute (LAM). The results show that Tepuk Tepung Tawar is a tradition originating from the Malay community and has been carried out since the time of the previous kings. Tepuk Tewar Tawar is done to express gratitude and prayer requests. The Tepuk Tepung Tawar tradition has several meanings in its implementation including a Malay expression regarding this tradition, the person doing the offering, the equipment used and the procedure for carrying out it. This tradition also has good values related to religious and psychological elements. Keywords: Tepuk Tepung Tawar, Malay Culture, Riau